2022
DOI: 10.5194/tc-2022-171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precursor of disintegration of Greenland's largest floating ice tongue

Abstract: Abstract. The largest floating tongue of Greenland’s ice sheet, Nioghalvfjerdsbræ, has so far been relatively stable with respect to areal retreat. Curiously, it experienced significant less thinning and ice flow acceleration than its neighbour Zacharias Isbræ. Draining more than 6 % of the ice sheet, Nioghalvfjerdsbræ might become a large contributor to sea level rise in the future. Therefore, the stability of the floating tongue is a focus of this study. We employ a suite of observational methods to detect r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The true orthophoto processing follows the common photogrammetric approach and with a given surface topography of the glacier, a mosaicing of the individual images is conducted. More details of the MACS‐Polar system can be found in [3]. The resulting mosaic of a crack tip is presented in Figure 2(B).…”
Section: Observation Of Crack Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The true orthophoto processing follows the common photogrammetric approach and with a given surface topography of the glacier, a mosaicing of the individual images is conducted. More details of the MACS‐Polar system can be found in [3]. The resulting mosaic of a crack tip is presented in Figure 2(B).…”
Section: Observation Of Crack Fieldsmentioning
confidence: 99%
“…A detailed analysis of the crack and the calving front (Figure 2B) was conducted in [3] and has shown that this crack is also a mode I crack. Therefore, it is comparable to the situation of the crevasse field.…”
Section: Simulated Stress Fieldmentioning
confidence: 99%
“…However, thinning has occurred over the last O. Zeising et al: Extreme melting of 79 • North Glacier 2 decades (Helm et al, 2014;Kjeldsen et al, 2015;Mouginot et al, 2015;Mayer et al, 2018), and cracks have formed at the calving front that might be a precursor to disintegration (Humbert et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The mass loss of the Greenland Ice Sheet over the last decades as a result of a warming atmosphere and ocean has accelerated (Shepherd et al, 2020) and contributed to recent sea-level rise by 1.4 mm a −1 (Khan et al, 2022a). Half of the mass loss is caused by ice-sheet discharge through marine-terminating glaciers (Shepherd et al, 2020), mainly due to the retreat of glacier fronts (King et al, 2020) as the floating ice tongues restrain the outflow of the grounded ice (Fürst et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its stability is attributed to pinning points at the calving front (Thomsen et al, 1997), lateral resistance from shear margins (Mayer et al, 2000;Rathmann et al, 2017;Mayer et al, 2018) and confinement of the glacier leading to lateral compression. However, thinning has occurred during the last two decades (Helm et al, 2014;Kjeldsen et al, 2015;Mouginot et al, 2015;Mayer et al, 2018) and cracks have formed at the calving front that might be a precursor of disintegration (Humbert et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%